Andragogy-Based Psychosocial Intervention and Funiculi Funicula Bibliotherapy to Strengthen the Meaning of Life Among Incarcerated Mothers at Class IIB Women's Prison Manado - Cynthia Maria Siwi; Ronald Jolly Pongantung; Dian Ratu Ayu Uswatun Khasanah (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Incarcerated mothers in Indonesia face severe psychological challenges, including loss of maternal identity, depression, and disrupted mother–child relationships during imprisonment. With 13,976 female inmates nationally and significant mental health needs, targeted psychosocial interventions are critically needed; however, they remain underrepresented in correctional rehabilitation programs. Objective: The Strengthening Life Meaning of Parenting for Incarcerated Mothers Program at the Class IIB Women’s Correctional Facility in Manado aims to enhance the psychological well-being of incarcerated mothers through the application of andragogy principles and the Funiculi Funicula novel series as a stress-coping mechanism. Methods: Activities were carried out using a group-based psychosocial development approach, including counseling, diary writing, creativity training, outbound experiential activities, and art exhibitions. The Funiculi Funicula novel series served as a medium for reflection and motivation, helping participants accept their past experiences and build renewed hope. Results: This program was evaluated using the Satisfaction With Life Scale (SWLS), showing an increase in mean “meaning in life” scores from 15.2 (slightly dissatisfied category) to 28.1 (satisfied category). As a result, participants experienced significant improvements in mental well-being, self-confidence, strengthening of the maternal role, and readiness for social reintegration. Conclusion: This model is expected to become a relevant correctional intervention for incarcerated mothers and may be applicable to other women’s correctional facilities.